Analisis Permasalahan Pengiriman Darat Palm Kernel dan Strategi Pengelolaan Vendor pada PT X - Grace Victory; Iwan Sukoco; Tribowo Rachmat Fauzan (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
This study investigates land transportation issues in the delivery of palm kernel at PT X and proposes a structured vendor management strategy. Despite relying on third-party vendors to enhance cost efficiency and flexibility, PT X faces frequent delays caused by a mismatch between planned and actual truck arrivals, poor road conditions, and the lack of a documented performance evaluation system. Using a qualitative approach, this research employs fishbone analysis to identify root causes from six dimensions: man, material, machine, method, environment, and measurement. The findings highlight that delivery delays are a multidimensional problem, requiring systematic improvements in both internal management and vendor coordination. This study recommends a data-driven vendor management strategy with enhanced documentation, standard operating procedures, and regular performance evaluation. Implementing these measures is expected to improve delivery efficiency, maintain product quality, and support sustainable logistics operations at PT X.